2008
DOI: 10.1002/ch.370
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of hypnotic analgesia in adults: A review of the literature

Abstract: This article both summarizes the previous reviews of randomized, controlled trials of hypnotic analgesia for the treatment of chronic and acute pain in adults, and reviews similar trials which have recently been published in the scientific literature. The results indicate that for both chronic and acute pain conditions: (1) hypnotic analgesia consistently results in greater decreases in a variety of pain outcomes compared to no treatment/standard care; (2) hypnosis frequently out-performs nonhypnotic intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 55 publications
(83 reference statements)
1
41
0
1
Order By: Relevance
“…HYPNOSIS AND HYPNOTIC SUGGESTIONS FOR CHRONIC PAIN As described above, hypnosis has been found to be an effective treatment for chronic pain across several conditions [15,16]. Studies have shown that approximately 70% of individuals with chronic pain are able to experience a short-term reduction in chronic pain during a treatment session or hypnosis practice, and between 20% and 30% achieve more permanent reductions in daily pain [15,40].…”
Section: Neurophysiological Mechanisms Involved In Pain Perception Anmentioning
confidence: 99%
See 4 more Smart Citations
“…HYPNOSIS AND HYPNOTIC SUGGESTIONS FOR CHRONIC PAIN As described above, hypnosis has been found to be an effective treatment for chronic pain across several conditions [15,16]. Studies have shown that approximately 70% of individuals with chronic pain are able to experience a short-term reduction in chronic pain during a treatment session or hypnosis practice, and between 20% and 30% achieve more permanent reductions in daily pain [15,40].…”
Section: Neurophysiological Mechanisms Involved In Pain Perception Anmentioning
confidence: 99%
“…Studies have shown that approximately 70% of individuals with chronic pain are able to experience a short-term reduction in chronic pain during a treatment session or hypnosis practice, and between 20% and 30% achieve more permanent reductions in daily pain [15,40]. There is also evidence to suggest that hypnosis may be more effective in treating neuropathic or vascular pain and less efficacious in treating primarily musculoskeletal pain (e.g., low back pain) [15]. There are two main theories on why hypnosis may work.…”
Section: Neurophysiological Mechanisms Involved In Pain Perception Anmentioning
confidence: 99%
See 3 more Smart Citations